PERTUMBUHAN IKAN BANDENG (Chanos chanos) ANTARA BENIH HATCHERY SKALA RUMAH TANGGA DAN GENERASI KEDUA (G-2) TERSELEKSI - Daniar Kusumawati; Zafran Jamaris; Titiek Aslianti (BERITA BIOLOGI, 2018)
Currently, there is a national concern regarding to the decrease of milkfish production from ponds in North Java due to a low quality of milkfish seed produced by small scale hatcheries in Bali, which is the main producer of milkfish seed. The quality of seed is strongly related to the quality of eggs (fertility), while quality of eggs produced depends on the management of brood stocks carried out by the hatcheries. Growth rate and growth hormone profiles are some of the biological aspects that could be used as a basis/benchmark to evaluate quality level of milkfish seed reared in ponds. The aim of this experiment was to evaluate growth rate and growth hormone profile performance between selected G-2 seed and small scale hatcheries seed as control population the growth rate. Research on grow-out of milkfish seed was conducted at the IMRAD ponds facility in Pejarakan, using milkfish seed produced by small scale hatcheries as well as selected second-generation (G-2) seed, each with the density of 5000 seed/pond (1 pond=0.5 ha). The seeds were fed with dry pellet and reared for 5 – 6 months. The results showed that the seed produced with standard operational procedure (SOP) by small scale hatcheries were having longer (F hit. = 13.68 > F tabel 1%) and heavier body washt (F hit. = 18.98 > F tabel 1%) better than selected G-2 seed and small scale hatcheries seed without SOP with high growth hormone concentration (F hit. = 4.95 > F tabel 5%).